Cu2‐xS Surface Phases and Their Impact on the Electronic Structure of CuInS2 Thin Films – A Hidden Parameter in Solar Cell Optimization. Issue 6 (1st February 2013) - Bär, Marcus; Klaer, Joachim; Weinhardt, Lothar; Wilks, Regan G.; Krause, Stefan; Blum, Monika; Yang, Wanli; Heske, Clemens; Schock, Hans‐Werner
Abstract The surface properties of CuInS2 (CIS) thin‐film solar cell absorbers are investigated by a combination of electron and soft X‐ray spectroscopies. Spatially separated regions of varying colors are observed and identified to be dominated by either CuS or Cu2S surface phases. After their removal by KCN etching, the samples cannot be distinguished by eye and the CIS surface is found to be Cu‐deficient in both regions. However, a significantly more pronounced off‐stoichiometry in the region initially covered by Cu2S can be identified. In this region, the resulting surface band gap is also significantly larger than the EgSurf of the initially CuS‐terminated region. Such variations may represent a hidden parameter which, if overlooked, induces irreproducibility and thus prevents systematic optimization efforts.